Modulation Technique in Clarifying the Implicature of Qur’anic Kin?yah Verses - Zalfa Khansa Nurfauzia; Mohamad Zaka Al Farisi; Hikmah Maulani (RETORIKA: Jurnal Ilmu Bahasa, 2024)
Modulation techniques are used when there is a gap in the lexical meaning of a translation, so a shift in semantic meaning is needed, such as a change in perspective, to avoid untranslatability in translation. This study analyzes the use of modulation techniques in translating Qur’anic kin?yah verses. Kin?yah is a figurative expression to describe something with a different meaning from its original. Therefore, translating kin?yah verses requires an in-depth understanding of the implicature hidden in the utterance. This study uses a qualitative approach with a content analysis method. The researcher will examine the content of the study of Qur’anic kin?yah verses and their translations from the Ministry of Religious Affairs. The research uses primary data sources in the form of Qur’anic kin?yah verses with a law theme due to differences of opinion among scholars and researchers. Then, the research analyzes the application of the modulation techniques and their implicature meaning based on relevance. The research finds that the Qur’anic kin?yah verses have shifted meaning from denotative to connotative, which aims to hide the original meaning and avoid inappropriate words. After analyzing the implicature meaning, it is found that the law-themed Qur’anic kin?yah verses contain majazi (connotative) meanings that refer to the meaning of intercourse as seven utterances, marriage as two utterances, and menstrual blood as one utterance. The shift in meaning has implications for better understanding and avoiding ambiguity in the translated text. Also, it contributes to the improvement of the readability and quality of translated Qur’anic verses.